MOF‐Derived Copper Nitride/Phosphide Heterostructure Coated by Multi‐Doped Carbon as Electrocatalyst for Efficient Water Splitting and Neutral‐pH Hydrogen Evolution Reaction. Issue 1 (9th January 2020) - Wang, Qijun; Zhang, Zheye; Zhao, Xuezhu; Xiao, Junwu; Manoj, Devaraj; Wei, Feifei; Xiao, Fei; Wang, Hairen; Wang, Shuai
Abstract: Efficient and robust electrocatalysts composed of earth‐abundant elements to replace noble metals is highly essential for cost‐effective production of hydrogen from water splitting. Herein, we demonstrate the fabrication of SO4 2− anions bridged MOF‐derived Cu3 N−Cu3 P heterostructure coated by ultrathin N, P, S‐tri‐doped carbon (NPSC) on nickel foam (Cu3 N−Cu3 P/NPSCNWs@NF) via an interface reconstruction strategy. The first‐principle simulation demonstrates that both Cu3 N, Cu3 P and NPSC own good electrical conductivity, suggesting these species can lead to efficient electrocatalytic performance. The remarkable features of high intrinsic conductivity and interfacial heterostructures at Cu3 N−Cu3 P/NPSCNWs@NF have ensured excellent water splitting electrocatalytic activity with a low potential of 1.54 V at 10 mA cm −2 in 1 M KOH over 24 h, and additionally the resultant electrode exhibits impressive response for HER with an ultralow potential of 109 mV at 10 mA cm −2 in neutral‐pH media over 30 h. Abstract : Interface reconstruction : A novel MOF‐derived copper nitride/phosphide heterostructure coated by ultrathin multi‐doped carbon (Cu3 N−Cu3 P/NPSCNWs@NF) electrode is successful fabricated via an interface reconstruction strategy for efficient overall water splitting in alkaline electrolyte and also shows highly efficient HER catalytic activity in neutral media.